EU anti-discrimination law - Ellis, Evelyn, 1948-; Watson, Philippa (Oxford : Oxford University Press, 2013)
'EU Anti-Discrimination Law' provides a detailed and critical analysis of the corpus of EU law prohibiting discrimination on the grounds of sex, racial or ethnic origin, religion or belief, disability, age, and sexual orientation. It takes into account the changes brought about by the Treaty of Lisbon and it contains thorough examination of the relevant case law of the Court of Justice of the EU. The book examines the background to the legislation and explains the essential characteristics and doctrines of EU law, in so far as they are relevant to the topic of anti-discrimination.
Previous ed.: 2005.
Description based on online resource; title from home page (viewed on Dec. 14, 2012).
Includes bibliographical references and index.
Keywords: Discrimination -- Law and legislation -- European Union countries